FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN TIMBULNYA GEJALA GASTRITIS PADA SISWA SEKOLAH MENENGAH ATAS KOTA JAMBI - Rahmawati Rahmawati (Jurnal Ilmiah Dikdaya, 2018)
Gastritis is an inflammation of the gastric mucosa that can be acute, chronic, diffuse or localized, the stomach is a digestive device that functions mechanically in storing food and drinks, breaking food into small particles, mixing with gastric fluid and gradually entering the intestine . The clinical picture of erosive acute gastritis varies from mild, asymptomatic, to very severe. Factors for gastritis are foods contaminated with bacteria, caffeine-containing drinks, alcohol, drugs such as non-steroidal anti-inflammatory drugs aspirin, acidic foods and drinks, spicy foods, and irregular diets. This research is an analytical study with a cross sectional approach. The sample of this study were students from Jambi City High School who were randomly drawn to get 930 samples. The results obtained from 930 respondents, most (61.3%) had chronic gastritis. And found a significant relationship between diet and the onset of symptoms of acute and chronic gastritis with P-Value = 0,000. Based on the results of this study, the researchers expect health information, especially regarding gastritis by local health workers so as to reduce the incidence of acute and chronic gastritis. Keywords: Acute Gastritis, Chronic Gastritis, Gastritis Factors